Swinging support? Economic cycles and changes in the public attitudes towards welfare recipients in Finland 1995 – 2010 - Susan Kuivalainen; Jani Erola (Turku Center for Welfare Research, 2022)
This article analyses the variation in public attitudes towards welfare recipients according to economic cycles. Previous research has indicated that economic recession leads to declining welfare state support, although some findings show stronger support during times of increased financial strain. The assumptions are tested with Finnish data. Finland provides ample opportunity to investigate the effects of situational factors, as it experienced two severe economic downturns during the period of examination. In contrast to many previous studies, we also considered whether the association between economic cycles and attitudes was dependent on socioeconomic status. Analyses reveal that high unemployment and economic downturns diminish public support for welfare provisioning. Furthermore, the results show that both individual and spousal unemployment, as well as social class position, are associated with people’s attitudes towards welfare recipients. These associations remain when the national unemployment rate and GDP growth rate are taken into account. Overall, the working class has stricter opinions of welfare recipients during economic downturns, whereas the opposite is true for the service classes and the self-employed. Moreover, men have stricter attitudes towards welfare recipients during economic recessions.